Transforming social media business models through blockchain - Upadhyay, Nitin (Emerald points., 2019)
Blockchain technology has the potential to disrupt and transform the social media business space, but the existing literature uses complex technical jargon that prevents practitioners from taking advantage of its full potential. Nitin Upadhyay overcomes this barrier and offers a uniquely accessible discussion of how blockchain can revolutionise social media business models. His book offers an up-to-date analysis of the real benefits, usage and operationalisation aspects of blockchain and provides a systematic framework for social media business transformation through blockchain technology, all while using a simple, practical terminology. Readers learn about the utility of the blockchain ecosystem, about the innovation value proposition available to social media platforms through blockchain and about how to develop, assess and evaluate change in social media business models. Ultimately, they learn how to utilise blockchain innovation to develop a decentralised, autonomous and distributed ecosystem within the social-media space. Transforming Social Media Business Models Through Blockchain is essential reading for stakeholders associated with social media, blockchain and management, including practitioners, leaders, and scholars working with industry partners.